Identification of dynamic properties of a flooded ballast layer using impact excitation technique and minimization algorithm - Ratabhat Wangtawesap; Chatpan Chintanapakdee; Chayut Ngamkhanong (Journal of Infrastructure Preservation and Resilience)
Abstract In recent times, the railway sector has faced a pressing need to expand its railway network, resulting in the widespread adoption of ballasted tracks. These tracks are favored for their ease of construction, making them a cost-effective solution for the railway industry. However, with global warming causing more volatile weather conditions leading to multiple occurrences of flooding in Thai railway structures. Ballast dynamic properties play a crucial role in the analysis of the performance and safety of the railway system. In response to these challenges, this study investigates how flooding affects the dynamic behavior of ballasted track structures. The impact hammering method is frequently used to evaluate the dynamic properties of ballasted tracks. However, previous studies have often simplified the analysis by treating the sleeper-ballast system as a single-degree-of-freedom (SDOF) system. This simplification overlooks the spatial variability in the conditions of the ballast layer. To achieve a more accurate representation, our study employs a multi-degree-of-freedom (MDOF) model, which considers the variability in the stiffness properties of the sleepers. The model for the sleeper-ballast system is constructed based on Timoshenko beam theory resting on an elastic foundation. Simulation of flooding on the ballast layer is conducted using a self-built wooden and acrylic box containing a full-scale track structure. This paper utilizes an instrumented impact hammering method, allowing for a comprehensive assessment of the dynamic properties of the ballast layer. To identify the dynamic characteristics of the ballast, a minimization algorithm is applied. The findings of this research indicate that as the water level rises, the stiffness decreases. This study provides crucial insights into how flooding impacts the dynamic properties of ballasted tracks, offering insights that can be applied to enhance the safety analysis of ballasted tracks in the future.